Eigenvalues and Eigenfunctions of Differential Operators with Involution - Kozhanov, A. I.; Bzheumikhova, O. I. (Siberian mathematical journal, 2024)
We demonstrate that the presence of summands with involution in the argument in an ordinary differential equation can significantly affect the well-posedness of the Cauchy and other problems. Furthermore, we show that the above effects can influence the well-posedness of classical boundary value problems for partial differential equations, particularly in the case of parabolic and pseudoparabolic equations.